Roles of Testosterone Replacement in Cardiac Ischemia-Reperfusion Injury - Pongkan W. (2017)
© SAGE Publications. Testosterone is an anabolic steroid hormone, which is the major circulating androgen hormone in males. Testosterone levels decreasing below the normal physiological levels lead to a status known as androgen deficiency. Androgen deficiency has been shown to be a major risk factor in the development of several disorders, including obesity, metabolic syndrome, and ischemic heart disease. In the past decades, although several studies from animal models as well as clinical studies demonstrated that testosterone exerted cardioprotection, particularly during ischemia-reperfusion (I/R) injury, other preclinical and clinical studies have shown an inverse relationship between testosterone levels and cardioprotective effects. As a result, the effects of testosterone replacement on the heart remain controversial. In this review, reports regarding the roles of testosterone replacement in the heart following I/R injury are comprehensively summarized and discussed. At present, it may be concluded that chronic testosterone replacement at a physiological dose demonstrated cardioprotective effects, whereas acute testosterone replacement can cause adverse effects in the I/R heart.